Primary isolated gingival tuberculosis - Rodrigues,Gabriel (2007)
Tuberculosis of the oral cavity is a rare event and when present is usually secondary to pulmonary tuberculosis. We present a case of a 33-year-old male patient who presented with symptoms of gingivitis. Local examination revealed multiple ulcers and a few nodules over the gingiva. A nodule biopsy was consistent with the diagnosis of gingival tuberculosis. The patient had no evidence of tuberculosis any where else in the body. Medical treatment was curative. As this condition is very rare, it is often over looked as it is never thought as a common clinical diagnosis. A biopsy is mandatory to establish diagnosis. The relevant literature is reviewed.